Microsoft Access 97 - Duffy , Tim; Microsoft Corporation (USA : Addison Wesley Publishing company, 1997)
Relational database management system that allows user to create tables, forms, queries, and reports from more than twenty customizable templates. Enables data entry and analysis from the Internet or an intranet utilizing HTML and hyperlinks.
"Upgrade"--Container.
Title from disc label.
0
0
Keywords: Database management; NUST; Relational databases